The Number and Potency of Endothelial Progenitor Cells in Type 2 Diabetes Mellitus Patients - Siska Darmayanti; Rini Hendriani; Cynthia Retna Sartika (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Type 2 Diabetes Mellitus (T2DM) is a metabolic disease, due to the disorder of insulin function, insulin secretion, or both. Long-term hyperglycemia conditions promote endothelial dysfunction precedes to the development of multiple organ dysfunctions. Endothelial progenitor cells (EPCs) and hematopoietic stem cell (HSCs) are the key cellular effectors of postnatal neovascularization and play central role in endothelial dysfunction. However, in T2DM condition, the number of apoptotic HSCs increase, it may cause the reduction in potency and number of EPCs. In diabetes, the circulating EPCs number decrease and their functionality is impaired,  but mechanism underlie of this impairement is unknown. The purpose of this study was to examine the relationship duration diabetes with  the number and potency of EPC cells in T2DM patients controlled and poorly controlled.METHODS: Thirty-eight T2DM male patients were classified into two group based on Indonesian Society of Endocrinology/Perkumpulan Endokrinologi Indonesia (PERKENI) criteria   on T2DM.  The   first   group   was a controlled glycemic condition group (hemoglobin A1c (HbA1C) <7.0%) and the second group was a poorly controlled glycemic condition group (HbA1C >7.0%). Cluster of differentiation (CD)34+ and CD133+ expressions were used as specific marker for EPC, while quantified bright aldehyde dehydrogenase (ALDHbr) assay was used to represented the potency of EPCs.RESULTS: This study showed that in poorly controlled T2DM group the number of EPCs was lower by 24.80% (p<0.05) compared to the T2DM controlled group. Similarly, the expression of ALDHbr was lower by 43.07% (p<0.05) in poorly controlled group.CONCLUSION: There was a decrease in the number and potency of EPCs in poorly controlled T2DM patients compared to the controlled T2DM patients. There was also a strong negative correlation between the duration of diabetes and number of EPCs.KEYWORDS: ALDHbr, endothelial progenitor cells, type 2 diabetes mellitus